IMF Survey, Volume 32, Issue 18. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 2003)
The IMF announced October 10 that its Executive Board had agreed on measures to enhance further the transparency of the institution, in particular by promoting the publication of more country documents. The agreement will be implemented following the Board's adoption, in the coming weeks, of specific amendments to its previous decision on transparency.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet